The relationship between knowledge about earwax cleaning with the grade of impacted cerumen in medical students - Asti Widuri; Intan Kusuma Ayu Setyaning Galih (Institute of Computer Science (IOCS), 2026)
The practice of using cotton buds for ear cleaning is common in the community. However, the use of cotton buds will cause various ear health problems. This study is needed to determine whether there is a relationship between knowledge about ear cleaning using cotton buds and the grade of cerumen impaction. Quantitative research using an observational analytic design with a cross-sectional approach. Sampling was carried out by simple random sampling using 37 respondents. The instrument used was a questionnaire and cerumen grade using otoscopy examination. The data were analyzed using chi square. Respondents who have a good level of knowledge (97.3%) have a sufficient level of knowledge (2.7%). The grade of cerumen in the right ear was grade 1 (13.5%), grade 2 (73.0%), grade 3, (10.8%), and grade 4 (2.7%). The left ear has the same as the right ear. There is no relationship between knowledge about the cleaning ears habits and the grade of cerumen with a p-value (0.381 > 0.05). Most respondents have a good level of knowledge. The knowledge about earwax cleaning not related with cerumen impaction grade.